ANALYSIS OF ACIDIC PROPERTIES OF DISTRIBUTION TRANSFORMER OIL INSULATION: A CASE STUDY OF JERICHO (NIGERIA) DISTRIBUTION NETWORK (Nigerian Journal of Technology, 2017)
This paper examined the acidic properties of distribution transformer oil insulation in service at Jericho distribution network Ibadan, Nigeria. Five oil samples each from six distribution transformers (DT1, DT2, DT3, DT4 and DT5) making a total of thirty samples were taken from different installed distribution transformers all from the Jericho distribution network. 10 g of the oil sample were dissolved in 40 ml of solvent ethanol in a ratio of 5 to 4. Then 0.1mol/litre of Potassium hydroxide (KOH) was added as titre with volume increments of 0.001 ml. The system detects when the acid-base-equivalence-point is reached by a voltage measurement in the solution. A transformer insulating oil passes acidity test if the acidity content is not more than   0.2 mg KOH/g oil according to the guideline from the American Society of testing Materials (ASTM). It was observed that twenty test samples of transformer insulating oil from four distribution transformers passed acidity test while ten samples from the remaining two failed the test, showing the later were in conditions. With the acidic content beyond the prescribed minimum value present in the transformer oil, transformer winding is at the risk excessive heat due to internal conduction that could cause explosion or fire outbreak in the transformerhttp://dx.doi.org/10.4314/njt.v36i2.32